2020
DOI: 10.17711/sm.0185-3325.2020.011
|View full text |Cite
|
Sign up to set email alerts
|

Role of parenting styles in internalizing, externalizing, and adjustment problems in children

Abstract: Introduction. Different studies have reported the relationship of parenting styles with adjustment problems in children. However, it has not been specified which aspects of parenting styles play a central role in the manifestation of such psychological problems. Objective. To increase the knowledge about the role of which parental educational styles are associated with internalizing, externalizing, and adjustment problems in Colombian children. Method. Through structural equations, the fit of the proposed mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 43 publications
0
13
0
5
Order By: Relevance
“…Many adolescents consume substances because they feel more adapted to the group, and if the group uses, the risk factor increases which may be associated with a greater perception of access to drugs (Alfonso et al, 2009;Pérez-Fuentes et al, 2015;Rueda Aguilar, 2020;Méndez et al, 2021). High values were also reached in family factors, such as the family risk of drug use; low family education on drugs; and therefore, a lack of norms concerning drug use, a permissive educational style, a lack of protective activities in the family, and family relationships (Pérez-Fuentes et al, 2015;Calero-Plaza et al, 2020;Moreno et al, 2020;Momeñe et al, 2021). In addition, the maladjusted group obtained higher scores in a higher level of global vulnerability to drug use (Alfonso et al, 2009;.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many adolescents consume substances because they feel more adapted to the group, and if the group uses, the risk factor increases which may be associated with a greater perception of access to drugs (Alfonso et al, 2009;Pérez-Fuentes et al, 2015;Rueda Aguilar, 2020;Méndez et al, 2021). High values were also reached in family factors, such as the family risk of drug use; low family education on drugs; and therefore, a lack of norms concerning drug use, a permissive educational style, a lack of protective activities in the family, and family relationships (Pérez-Fuentes et al, 2015;Calero-Plaza et al, 2020;Moreno et al, 2020;Momeñe et al, 2021). In addition, the maladjusted group obtained higher scores in a higher level of global vulnerability to drug use (Alfonso et al, 2009;.…”
Section: Discussionmentioning
confidence: 99%
“…This may indicate that the at-risk group was at risk of a possible imbalance and that the perception of the student being able to access drugs if they wanted was high (Alfonso et al, 2009). In the same way, the family can pose a risk for consumption due to risky or conflictive situations, drug use in the family environment, or low family education about the risks of drugs (Pérez-Fuentes et al, 2015;Kuntsche and Kuntsche, 2016;Calero-Plaza et al, 2020;Moreno et al, 2020). Therefore, these results are indicators that this requires action so that the moderate values do not suppose a situation of greater risk and that the student can have maladjusted behaviors and therefore put their health at risk (Cerezo et al, 2013;Molero et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…examined 45 parents and their children, and found that among support, satisfaction with parenting, commitment, communication, discipline, and autonomy, commitment was the only parental attitude related to anxiety symptomatology. Moreno-Méndez et al (2020) have examined democratic, ambiguous, authoritarian and permissive parenting styles among 422 Colombian parents and their children and found the permissive style to be associated with anxiety and depression.…”
Section: Internalizing Symptoms Among Colombian Youthmentioning
confidence: 99%
“…Since this initial categorization of parenting styles, other models have emerged. Examples from recent research include the concepts of rejection (Mȃirean & Diaconu-Gherasim, 2020), and democratic and ambiguous parenting styles (Moreno-Méndez et al, 2020).…”
Section: Introductionmentioning
confidence: 99%